Analisis Limbah Material Pekerjaan Arsitektural pada Pembangunan Perumahan Subsidi Di Kota Langsa - Indah Syahputri; Firdasari Firdasari; Nova Purnama Lisa (Jurnal Serambi Engineering, 2023)
Abstract Residual construction material is defined as something that is more than what was planned, both from the results of the work and the remaining, damaged, or lost material so that it can no longer be used according to its intended purpose. From the results of observations that have been made in several subsidized housing locations in Langsa City, there are many leftover materials from architectural work, because of that it is necessary to do an analysis of the type of waste material, the causes of waste and waste prevention measures that are often carried out. The method in this study uses descriptive statistical methods using Kendall's W so that rankings are obtained for variables, types of waste material, factors that cause waste, and waste prevention actions that are often carried out. The results of this study, the type of material that has the largest quantity is sand with a total score of 97, cement with a total score of 93, and red brick with a total score of 45. The dominant factor causing the amount of remaining architectural work material in subsidized housing is external factors with a total score of 116, material management with a total score of 83, and workers with a total score of 80. Then the form of preventive action that can minimize the waste of material that is often done is checking periodically (monitoring) with a total score of 125, purchasing materials as needed with a total score of 125, and increased coordination between workers with a total score of 124.